Efficacy of a Primary Care-Based Mobile Application to Increase Hepatitis C Screening Among Asian Americans: A Secondary Analysis of a Randomized Clinical Trial. (7th January 2023) - Khalili, Mandana; Kim, Nicole J; Tsoh, Janice Y; Walsh, Judith M E; Elizabeth Goldman, L; Park, Helen; Lau, Ivy; Wong, Ching; Gildengorin, Ginny; Nguyen, Tung T
Abstract: Background: Hepatitis C virus (HCV) screening remains suboptimal. We assessed the efficacy of a mobile application and provider alert in enhancing HCV screening among Asian Americans. Methods: A secondary analysis of a cluster-randomized clinical trial was performed during the birth cohort screening era to assess the efficacy of a Hepatitis App (intervention), a multilingual mobile application delivering interactive video education on viral hepatitis and creating a Provider Alert printout, at primary care clinics within 2 healthcare systems in San Francisco from 2015 to 2017. A comparison group received usual care and a similar intervention on nutrition and physical activity. The outcome was electronic health record (EHR) documentation of HCV screening along with patient-provider communication about testing and test ordering. Results: Four hundred fifty-two participants (mean age 57 years, 36% male, 80% foreign-born) were randomized by provider clusters to the intervention (n = 270) or comparison groups (n = 182). At 3-month follow up, the intervention group was more likely than the comparison group to be aware of HCV (75% vs 59%, P = .006), to discuss HCV testing with their providers (63% vs 13%, P < .001), to have HCV testing ordered (39% vs 10%, P < .001), and to have EHR-verified HCV testing (30% vs 6%, P < .001). Within the intervention group, being born between 1945 and 1965 (odds ratio, 3.15; 95% confidence interval, 1.35–7.32) was associated with increased HCV testing. Conclusions: The Hepatitis App delivered in primary care settings was effective in increasing HCV screening in a socioeconomically diverse Asian American cohort. This highlights the importance of mobile technology as a patient-centered strategy to address gaps in HCV care. Abstract : In this cluster-randomized clinical trial, the Hepatitis App, a multilingual mobile application and provider alert, increased hepatitis C virus (HCV) awareness, patient-provider discussion about HCV, and laboratory-verified HCV screening rates in a socioeconomically diverse Asian American cohort.